Hydrogen economies and energy futures: A new Australian dream?. (September 2022) - Beasy, Kim
Abstract: Australia, like many other places in the world, is significantly investing in hydrogen technologies. In this perspective piece, I discuss how the socio-political context has shaped, and is continuing to influence, the approach to advancing a hydrogen economy in Australia. I detail the historical events that have influenced Australia's ambitions of global leadership in hydrogen energy and through doing so, reveal future opportunities and challenges. I argue that investment in hydrogen technologies reflects ecomodernist and technocratic ideologies, and that deeper engagement with sociotechnical and socio-political dimensions are needed to assure hydrogen becomes the dream that so much of the world is relying on it to be.